Pile group in clay under cyclic lateral loading with emphasis on bending moment: Numerical modelling. Issue 3 (4th March 2023) - Nimbalkar, Sanjay; Basack, Sudip
Abstract: Pile foundations supporting major structures are often founded in soft compressible clays. Apart from usual super-structural loading, these piles are subjected to cyclic lateral loads originating from actions of waves, ship impacts, winds or moving vehicles. Such repetitive loading induces stress reversal in adjacent soft clay initiating progressive degradation in soil strength and stiffness. This not only deteriorates the pile capacity with unacceptable displacements, the bending moments also increase. Although past studies investigated the response of single pile under lateral cyclic loading, a detailed study on pile group in clay under cyclic lateral loading with emphasis on bending moment is of immense practical interest. This paper focuses on detailed study of the response of pile group in clay under cyclic lateral loading, with emphasis on bending moment, through numerical modelling via a three-dimensional dynamic finite element (FE) approach and simplified boundary element modelling (BEM). Comparisons of computed results with available test data imply that the results obtained by 3 D dynamic FE model are better than the BEM. Extensive parametric studies with field data indicate that pile bending moment has been significantly influenced by cyclic loading parameters (number of cycles, frequency and amplitude). Relevant conclusions are drawn from the entire study.